ANALISIS SISTEM INFORMASI MANAJEMEN DALAM STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PRODUK UMKM (STUDI KASUS PADA UMKM KERIPIK MAKROS JAYA ABADI PONTIANAK) - Heny Hidayati; Julianto (Faculty of Islamic Economics and Business, 2023)
SME are productive businesses owned by individuals or business entities that have met the criteria for micro-enterprises. In its development, the role of SME can improve the community's economy because the business is easy, the capital and risks are small, promising, and can assist government programs in alleviating poverty and unemployment. The problem that occurs in the development of SME is the difficulty for SME business actors in marketing their products so that they are of interest to consumers, so that they reach and are widely accepted at several regional points. The purpose of this research is to be able to see the results of an analysis of Management Information Systems in a Marketing Strategy to Increase Sales of SME Makros Jaya Abadi Pontianak Chips Products. Analyzing the marketing strategies used by these SME in developing their business. The research method used is the Qualitative Method with data collection techniques namely interviews and literature studies. In developing its business, SME Makros Chips uses various strategies in marketing management including Marketing Strategy, Targeting Strategy, Positioning Strategy, and Marketing Mix. Keywords : SME, Makros Chips, Marketing Strategy.